The Acceptance of Utilizing Steel Slag in Concrete Among Construction Stakeholders - Mohd Noh, Hamidun; Sukadis Samsu Djatmiko, Siti Nursyafiqah; Idris, Nur’ain; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam (Research in Management of Technology and Business, 2021)
In construction industry, cement is important for the production of concrete. It is also a binder, a substance used for construction that sets, hardens, and adheres to other materials to bind them together. Unfortunately, manufacturing process of cement contributes the greenhouse gases which harmful the environment. On the other hand, steel slag which has a huge potential to be utilize in concrete as replacement material could be used as an alternative material in concrete. The needed to improve the use of steel slag is an effective way to solve these problems. The objectives of this study are to determine the factors that influence the concrete production, to observe the future acceptance to produce concrete using the steel slag among concrete manufacturer, to identify the initiative in managing by product of steel and improving the product in the market. The methodology of this research uses consistency approaches by interviewing a concrete supplier from Inno Concrete Technologies Sdn. Bhd, Seng Foong Concrete Sdn. Bhd and Renggam Concrete. The finding show that all factors stated influence the choice of materials in concrete manufacturing. From the qualitative analysis, respondents agreed that the use of steel slag could be an alternative material in concrete but required a lot of improvement to be accepted in the industry besides aiming to reduce the environment impact from production of cement. Thus, it is anticipated that the objective of this analysis will have a possible to contribute as an alternative material and also towards better future in this field..